2015
DOI: 10.4238/2015.december.14.12
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the association between the rs7903146 polymorphism at the TCF7L2 locus and type 2 diabetes mellitus susceptibility

et al.

Abstract: ABSTRACT. Type 2 diabetes mellitus (T2DM) is a chronic disease caused by genetic and environmental factors. T2DM has been associated with specific polymorphisms in the TCF7L2 gene. This study evaluates the relationship between the rs7903146 locus polymorphism of the TCF7L2 gene and T2DM susceptibility through meta-analysis; the overall aim is to provide a basis for evidence-based medicinal treatment of T2DM. Cohort and case-control studies from Medline, PubMed, EMBASE, CBM, CNKI, and academic conferences/disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…Similar findings were found in a meta-analysis conducted by Peng et al ( 14 ), which revealed that -47833C>T and -98368G>T variants are associated with higher type 2 diabetes risk. Similarly, meta-analysis results reported by Liu et al ( 15 ) and Dou et al ( 16 ) showed a significant association between -47833C>T and type 2 diabetes susceptibility in different populations. Our findings are in agreement with those reported by Chandak et al ( 29 ), who showed that -98368TT genotype increases fasting plasma glucose levels in the Indian population and that both of the most common variants are associated with type 2 diabetes in diabetic and nondiabetic individuals.…”
Section: Discussionsupporting
confidence: 54%
“…Similar findings were found in a meta-analysis conducted by Peng et al ( 14 ), which revealed that -47833C>T and -98368G>T variants are associated with higher type 2 diabetes risk. Similarly, meta-analysis results reported by Liu et al ( 15 ) and Dou et al ( 16 ) showed a significant association between -47833C>T and type 2 diabetes susceptibility in different populations. Our findings are in agreement with those reported by Chandak et al ( 29 ), who showed that -98368TT genotype increases fasting plasma glucose levels in the Indian population and that both of the most common variants are associated with type 2 diabetes in diabetic and nondiabetic individuals.…”
Section: Discussionsupporting
confidence: 54%
“…The TCF7L2 gene harbours several single nucleotide polymorphisms (SNPs) in strong linkage disequilibrium that tag the strongest genetic association with Type 2 diabetes . The TCF7L2 SNP with the most robust association and consistency across races/ethnicities of individuals with Type 2 diabetes is rs7903146, widely considered the causal variant at this locus .…”
Section: Introductionmentioning
confidence: 99%
“…TCF7L2 expression is related to its proposed function in insulin secretion. Several previous studies have examined the role of the TCF7L2 rs7903146 polymorphism in the development of type 2 diabetes mellitus, but their results have been inconclusive (Assmann et al, 2014;Barros et al, 2014;Allahdini et al, 2015;GuewoFokeng et al, 2015;Liu et al, 2015;Nanfa et al, 2015;Yao et al, 2015;Yang et al, 2015). In this study, we conducted a hospital-based case-control investigation to evaluate the relationship between TCF7L2 rs7903146 and risk of developing type 2 diabetes mellitus in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%